An alternative design for controlling compound mixing in a tire factory - Teoh, Siang Choon; Pakorn Adulbhan; Prapon Vongvichien; Tang, John C.S.; RED (USAID) (Bangkok : Asian Institute of Technology, 1980)
The primary objective of this study is to develop an alternative quality design plan for the mixing system. The effects of average outgoing quality limit, changes in costs and inspection errors on these sampling plans are considered. A review of previous works on optimal sampling plan and process control is done. A model based on a model of a dynamic problem is developed. After adapting the model to the real system, the constraints imposed reduced the model to a static problem. A set of general optimal sampling plans are derived for the purpose of analyzing the situation and the effects of cost ratios on them. An analytical solution for the transition state of sampling is included. The raw data collected is of variable type. With known specification limits, the "defects" are identifiable, hence the defects are treated as "attribute" defects and not "variable" defects. Computer programs are used to derive the numerical results, search for the optimal sampling plans and calculate the performance measures of these plans. A step by step procedure is employed.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1980
Keywords: Tire industry -- Quality control